Physical activity in birth cohorts of three Brazilian cities (Ribeirão Preto, Pelotas, and São Luís): A cross-sectional study - Susana Cararo Confortin; Paulo Ricardo Higassiaraguti Rocha; Bruna Gonçalves Cordeiro da Silva; Ana Maria Baptista Menezes; Bernardo Lessa Horta; Helen Gonçalves; Heloisa Bettiol; Marco Antonio Barbieri; Maria da Conceição Pereira Saraiva; Maria Teresa Seabra Soares de Britto e Alves; Rosângela Fernandes Lucena Batista; Viviane Cunha Cardoso; et al. (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT Objective: To describe the prevalence of physical activity among subjects from birth cohorts of three cities located in different regions of Brazil according to sociodemographic characteristics and sex, comparing the relationships within and between cohorts. Methods: Cross-sectional study involving 12,724 adolescents and young adults who participated in five birth cohorts: Ribeirão Preto [1978/79 (37/39 years old in 2016) and 1994 (22 years in 2016)]; Pelotas [1982 (30 years in 2012) and 1993 (22 years in 2015)], and São Luís [1997/98 (18/19 years in 2016)]. Leisure-time physical activity was evaluated with questionnaires (insufficiently active: <150 min/week and active: ≥150 min/week) and moderate and vigorous physical activity (MVPA) was objectively measured by accelerometry. Those, in each city, were evaluated accordingly to skin color, socioeconomic classification, and study/work activities. Results: The prevalence of leisure-time physical activity ranged from 29.2% at 30 years old in Pelotas to 54.6% among adolescents from São Luís. The prevalence of leisure-time physical activity was higher among younger people (54.6% in São Luís 1997), while the same was not observed for total physical activity. MVPA (3rd tercile) was higher in the cohorts from Pelotas and São Luís. The prevalence of leisure-time physical activity and MVPA was higher in men. The data showed that the variation in physical activity was associated with sex and sociodemographic conditions in all cohorts. Conclusion: Sociodemographic characteristics should be considered when promoting leisure-time physical activity and actions aimed at young people, and adults who are more socioeconomically vulnerable should be encouraged.